Viewing a Face (Especially One's Own Face) Being Touched Enhances Tactile Perception on the Face - Serino, Andrea; Pizzoferrato, Francesca; Làdavas, Elisabetta (Psychological science, 2008)
Observing touch on another person's body activates brain regions involved in tactile perception, even when the observer's body is not directly stimulated. Previous work has shown that in some synaesthetes, this effect induces a sensation of being touched. The present study shows that if perceptual thresholds are experimentally manipulated, viewing touch can modulate tactile experience in nonsynaesthetes as well. When observers saw a face being touched by hands, rather than a face being merely approached by hands, they demonstrated enhanced detection of subthreshold tactile stimuli on their own faces. This effect was specific to observing touch on a body part, and was not found for touch on a nonbodily stimulus, namely, a picture of a house. In addition, the effect was stronger when subjects viewed their own faces rather than another person's face. Thus, observing touch can activate the tactile system, and if perceptual thresholds are manipulated, such activation can result in a behavioral effect in nonsynaesthetes. The effect is maximum if the observed body matches the observer's body.